Detecção de anticorpos anti-Trypanosoma spp. em bovinos do Rio Grande do Sul - Samoel, Gisele Vaz Aguirre (2023)
Trypanosomosis is an important disease for cattle production in which Trypanosoma vivax is considered the main species causing the disease in South America. This disease has characteristics of being chronic and debilitating, resulting in high economic losses that are complex to be estimated. The presence of antibodies in populations is often used for epidemiological studies and geographical distribution of this disease, because it reflects the presence of previous exposure of the animals to the protozoan. Currently, Rio Grande do Sul (RS) is considered a non-endemic region for T. vivax, and the species has already been described causing natural infections in cattle and horses in the central region of the state, but there are still no occurrence studies or epidemiological data on the parasitism of this species in cattle in the state. Therefore, the objective of this research was to detect the presence of antiTrypanosoma spp. antibodies in cattle herds in RS and to suggest which intermediate regions of the state can be considered risk areas for the transmission of T.vivax. For this, 691 samples of bovine serum from the serum bank of the Laboratório de Doenças Parasitárias – UFSM were analyzed, selected according to the effective number of cattle in RS, and grouped according to their intermediate region of origin. The RS is subdivided into 7 intermediate regions named: Uruguaiana, Santa Maria, Porto Alegre, Passo Fundo, Ijuí, Caxias do Sul, Santa Cruz do Sul, e Pelotas; Antibody detection was performed using the Indirect Immunofluorescence Reaction (IFAT) technique, using trypomastigotes forms of T. vivax fixed on slides. The samples were tested at a 1:80 dilution and incubated for 50 minutes at 37oC in a humid and dark chamber; the secondary antibody (Anti- bovine IgG) was used at a dilution of 1:200, and incubated under the same conditions described. The overall seroprevalence of anti- Trypanosoma spp. in cattle it was 24.6% (170/ 691) in the analyzed samples. The detection rate ranged from 0% to 37% in the study regions, with a higher prevalence in the intermediate region of Ijuí (37.3%), Uruguaiana (30.7%) and Passo Fundo (28.9%), which were suggested as risk areas for bovine trypanosomosis due to the high seroprevalence detected. The lowest prevalences were observed in Pelotas (24.3%), Santa Cruz do Sul (23.0%), Porto Alegre (17.5%), Santa Maria (5.7%) and Caxias do Sul (0%). A total of 24 herds were analyzed, where at least one positive sample was detected in 21 herds (89.6%) and 3 herds had no positive sample (13.3%). In positive herds, the detection frequency rate ranged from 4.2% to 63.6%. This is the first serological study in Rio Grande do Sul to determine the infection status of Trypanosoma spp. in cattle, promoting information on the occurrence and distribution of bovine trypanosomosis in the state.